GONE GIRL DARI DAVID FINCHER: DESKRIPTIF GEJALA PSIKOPAT DITUNJUKKAN OLEH KARAKTER AMY ELLIOT DUNNE [David Fincher’s Gone Girl: Description of Psychopathic Symptoms Reflected on Amy Elliot Dunne’s Character] - Rodelio Paparang Lalenoh (Kantor Bahasa Provinsi Maluku, 2017)
This research was intended to reveal the psychopathic symptoms that shown by Amy Elliot Dunne’s in Gone Girl film by applying Dr. Hare’s Psychopathy Checklist-Revised 2nd Version (PCL-R) as the main theory of the whole description in the film. The writer used descriptive-qualitative method to simply collect all the data from accessible books, journal, and official website. Furthermore, these were used to analyze the psychopathic symptoms through the character’s behavior, dialogue, monologue, and narration. The writer revealed Nick’s disloyal lifestyle to his marriage and followed by Nick’s cheating on Amy drive Amy to be a psychopath. Conclusively, the writer reveals psychopathic symptoms depicted on Amy: Glib and Superficial Charm, Pathological Lying, Conning and Manipulative, Lack of Remorse and Guilt, Callous and Lack of Empathy, Shallow Affect, Parasitic Lifestyle, Poor Behavioral Control, Promiscuous Sexual Behavior, and Criminal Versatility. Penelitian berikut bermaksud untuk mengungkap gejala-gejala psikopat yang di tunjukan oleh Amy Elliot Dunne di film Gone Girl dengan mengaplikasikan Psychopathy Checklist Revised Versi ke-2 (PCL-R) milik Dr. Hare sebagai teori utama di semua deskripsi pada film tersebut. Penulis menggunakan pendekatan deskriptif-kualitatif untuk mengumpulkan semua data dari buku yang dapat diakses, jurnal, dan website resmi. Selebihnya, ini akan digunakan untuk menganalisa gejala-gejala psikopat melalui sifat karakter, dialog, monolog, dan narasi. Penulis mengungkapkan cara hidup Nick yang tidak setia terhadap pernikahan dan diikuti oleh Nick yang selingkuh terhadap Amy memicu Amy menjadi psikopat, Kesimpulannya, penulis mengungkapkan gejala yang di tunjukan Amy: Glib and Superficial Charm, Pathological Lying, Conning and Manipulative, Lack of Remorse and Guilt, Callous and Lack of Empathy, Shallow Affect, Parasitic Lifestyle, Poor Behavioral Control, Promiscuous Sexual Behavior, dan Criminal Versatility.